Annual Plan 1996-97 - Planning Commission (Planning Commission, 1996)
The Eighth Five Year Plan (1992-97) was launched immediately after the initiation of a set of stabilisation and structural adjustment measures by the Government in 1991 (termed as "Economic Reforms"), which were designed to combat the then prevailing crisis in the balance of payments (BoP) and resources position of the Government. The Plan took into account some of the changes that were expected to come about due to economic reforms.
Government of India Planning Commission
Government of India Planning Commission